A gravity waves study close to the Andes mountains in Patagonia and Antarctica with GPS radio occultation observations - Alexander, Pedro Manfredo (2010)
We first study the seasonal and geographical behavior of gravity wave activity in the lower stratosphere over the southernmost Andes mountains and their prolongation in the Antarctic Peninsula by global positioning system (GPS) radio occultation (RO) temperature profiles, obtained between years 2002 and 2005 by the CHAllenging Minisatellite Payload (CHAMP) mission. The observed features complement observations in the same zone by other satellite passive remote sensing instruments, which are able to detect different height regions and other spectral intervals of the wave spectrum. Comparisons with previous GPS RO studies in smaller areas than the one covered in our analysis are also established. Significant seasonal variation of wave activity is observed in our work, in agreement with results from other instruments. The locations of significant cases indicate that topography is an important source. Some strong wave activity is also found over open ocean. Critical level filtering is shown to have an attenuation effect, implying that a large fraction of the observed activity can be considered to be an outcome of mountain waves. The studied region has a significant advantage as compared to other regions of our planet: it generates wavefronts nearly aligned with the North-South direction (almost parallel to the mountains), whereby this geometry favors the wave detection by the nearly meridional line of sight characterizing most of the GPS RO observations used. A distribution of the observed gravity waves in terms of amplitudes and wavelengths is also presented.